Wicked : the soundtrack [compact disc] - Schwartz, Stephen; Schwartz, Stephen (Republic Records, 2024)
Features performances by the stars of Universal Pictures' new cinematic event, Wicked, with music and lyrics by legendary Grammy and Oscar winning composer and lyricist Stephen Schwartz. The soundtrack includes songs performed by Emmy, Grammy, and Tony winning powerhouse Cynthia Erivo as Elphaba and Grammy-winning, multi-platinum recording artist and global superstar Ariana Grande as Glinda. In addition, the soundtrack features the musical talents of Michelle Yeoh as Shiz University's regal headmistress Madame Morrible; Olivier Award winner and Emmy nominee Jonathan Bailey as Fiyero, a roguish and carefree prince; and pop culture icon Jeff Goldblum as the legendary Wizard of Oz. Based on one of the most beloved and enduring musicals on stage for the past two decades, the spectacular, generation-defining film adaptation of Wicked is destined to be the most talked-about films of the holiday season. The official soundtrack track list includes iconic Wicked songs "Defying Gravity," "Popular," "Dancing Through Life" and more, performed as you've never heard them before!